Climate determines vascular traits in the ecologically diverse genus Eucalyptus - Sebastian Pfautsch; Marco Harbusch; Anita Wesolowski; Renee Smith; Craig Macfarlane; Mark G. Tjoelker; Peter B. Reich; Mark A. Adams (Ecology Letters, 2016)
Current theory presumes that natural selection on vascular traits is controlled by a trade‐off between efficiency and safety of hydraulic architecture. Hence, traits linked to efficiency, such as vessel diameter, should show biogeographic patterns; but critical tests of these predictions are rare, largely owing to confounding effects of environment, tree size and phylogeny. Using wood sampled from a phylogenetically constrained set of 28 Eucalyptus species, collected from a wide gradient of aridity across Australia, we show that hydraulic architecture reflects adaptive radiation of this genus in response to variation in climate. With increasing aridity, vessel diameters narrow, their frequency increases with a distribution that becomes gradually positively skewed and sapwood density increases while the theoretical hydraulic conductivity declines. Differences in these hydraulic traits appear largely genotypic in origin rather than environmentally plastic. Data reported here reflect long‐term adaptation of hydraulic architecture to water availability. Rapidly changing climates, on the other hand, present significant challenges to the ability of eucalypts to adapt their vasculature.